2015
DOI: 10.1111/bph.13045
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic anti‐tumour effects of tetrandrine and chloroquine combination therapy in human cancer: a potential antagonistic role for p21

Abstract: BACKGROUND AND PURPOSETetrandrine, a bisbenzylisoquinoline alkaloid isolated from the Chinese medicinal herb Stephaniae tetrandrae, has a long history in Chinese clinical applications to treat diverse diseases. Tetrandrine induced apoptosis or, at low concentrations, autophagy of human hepatocellular carcinoma cells. Here we have tested the effects of inhibitors of autophagy such as chloroquine, on the response to low concentrations of tetrandrine in cancer cells. EXPERIMENTAL APPROACHCultures of several cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 61 publications
2
34
0
Order By: Relevance
“…This may explain why DU145 cells exhibited the highest sensitivity towards Tet in all of the 11 cell lines tested (1). It has been reported that CQ enhances the anti-tumor effects in cancer cells (19). The results of the present study indicated that lysosomal pH is able to affect Tet-induced cell death.…”
Section: Discussionsupporting
confidence: 57%
“…This may explain why DU145 cells exhibited the highest sensitivity towards Tet in all of the 11 cell lines tested (1). It has been reported that CQ enhances the anti-tumor effects in cancer cells (19). The results of the present study indicated that lysosomal pH is able to affect Tet-induced cell death.…”
Section: Discussionsupporting
confidence: 57%
“…STOCK1N-35874 is a cytotoxic quinoline alkaloid that inhibits the DNA enzyme topoisomerase, which is isolated from the bark and stem of Camptotheca acuminata (39). STOCK1N-35874 showed marked anticancer activity in preliminary clinical trials, and its analogues have been used in cancer chemotherapy (40,41). 5182598 is considered to be an important anticancer drug from the group of benzylisoquinoline alkaloids (42).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have suggested that CQ can inhibit autophagy through the prevention of lysosome acidification, and subsequently, the inhibition of autophagosome-lysosome fusion, to block the degradation of autolysosomes at the last step of autophagy (8,9). Previous studies have indicated that CQ exhibited an antitumor effect on several types of cancer, including glioblastoma (10,11), hepatocellular carcinoma (12), breast cancer (13), prostate cancer (14) and pancreatic cancer (15), which prompts us to hypothesize that CQ may be able to influence the growth of esophageal carcinoma through the modulation of autophagy. Therefore, the aim of the present study is to explore the antitumor effect of CQ on the esophageal squamous carcinoma cell line EC109, and the potential mechanism for this effect.…”
Section: Introductionmentioning
confidence: 99%